Produktivitas Tiga Genotipe Kedelai dengan Air Berbeda dan Kedalaman Muka Air pada Berbagai Kondisi Tanah di Pasang Surut - Pujiwati, Hesti; Aziz, Sandra A.; Ghulamahdi, Munif; Yahya, Sudirman; Haridjaja, dan Oteng (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
ABSTRACTSoybean extensification on mineral and peaty mineral soils of tidal land are limited by Al and Fe toxicity.  Modification of growing environment and the use of tolerant variety are the possible alternatives to overcome the limitation.  The research was aimed to study soybean productivity in various soil types with different depth of water level and different water compositions. The experiment was held under mineral, peaty mineral soils with interaction types B and C  of tidal swamp in Banyuasin, South Sumatera from May to August 2014.  At each location, there was a three factor experiment was arranged in a split-split plot design. The first factor was two water depth (10 and 20 cm), the second factor was three varieties (Tanggamus, Cikuray, Ceneng) and third factor was three different water compositions (river water, peat water, high-tide water). The results showed productivity on mineral soil types C, peaty  mineral soil types B, and mineral soil types B were 4:50, 3.65, 0:32 ton ha-1 respectively. In peaty mineral soil types B, Ceneng with a depth of 20 cm water level resulted in highest productivity. In the mineral soil overflow type B, Cikuray with peat water composition had highest productivity.Keywords: mineral, peaty mineral, sensitive, tolerant